Prove that cos(A+B)+sin(A-B)=2sin(45°+A)cos(45°+B)
in Trigonometry Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

2 Answers

Best answer

sin(45+A)=sin45cosA+cos45sinA=(cosA+sinA)/√2; similarly cos(45+B)=(cosB-sinB)/√2.

Let A = 2sin(45+A)cos(45+B) = (cosA+sinA)(cosB-sinB) = cosAcosB-cosAsinB+sinAcosB-sinAsinB.

cos(A+B)=cosAcosB-sinAsinB; sin(A-B)=sinAcosB-cosAsinB.

So A=(cosAcosB-sinAsinB)+(sinAcosB-cosAsinB)=cos(A+B)+sin(A-B) QED.

by Top Rated User (787k points)
To prove cos(A+B)+sin(A-B)=2sin(45°+A).cos(45°+B) LHS: cos(A+B)+sin(A-B) =(cosAcosB-sinAsinB)+(sinAcosB-cosAsinB) =cosAcosB-sinAsinB+sinAcosB-cosAsinB Now take RHS =2sin(45°+A).cos(45°+B) Using Identity of sin(A+B) and cos(A+B) =2( (sin45°.cosA + cos45°.cosA).(cos45°.cosA - sin45°sinA) ) Now put value of cos 45°=1/√2 and sin 45°=1/√2 By putting values we get =2( (1/√2×cos A+1/√2×sinA).(1/√2cosB-1/√2sinB) ) Now take LCM. 2 [{(cosA+sinA)÷√2 }.{(cosB-sinB)÷√2}]. Now multiple the terms inside the bracket =2[(cosAcosB+sinAcosB-sinAcosB-sinAsinB)÷(√2×√2)] = 2{(cosAcosB-sinAsinB+sinAcosB-cosAsinB)÷(2)} Now 2 get cancelled with the 2 in the denominator =cosAcosB-sinAsinB+sinAcosB-cosAsinB Now LHS=RHS Hp

Related questions

Welcome to, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
85,412 questions
90,932 answers
103,318 users